Uterine Tumors Resembling Ovarian Sex Cord Tumors: A Case Report of Conservative Management in Young Women. Issue 4 (1st April 2009) - Berretta, Roberto; Patrelli, Tito S.; Fadda, Giovanni M.; Merisio, Carla; Gramellini, Dandolo; Nardelli, Giovanni B.
Abstract : Abstract: Uterine tumors resembling ovarian sex cord tumors (UTROSCT) are distinguished into two separate groups: endometrial stromal tumors with sex cord-like elements (Group I), which have an unfavorable prognosis; and UTROSCT proper (group II), with more than 40% sex cord-like differentiation and less endometrial component, which are biologically less aggressive than the tumors of the other group. We report the case of a young woman with UTROSCT treated by minimally invasive hysteroscopic surgery. This is one of the few cases reported in the literature that have been managed conservatively.